Prove algebraically that n^3 +3n -1 is odd for all positive integers n

There are 2 possible cases.

First when n is even, then let n = 2k where k is a positive integer.
Substituting n = 2k gives us:
(2k)3 + 3(2k) -1
= 8k3 + 6k - 1
[We are trying to prove that it is odd so try and write it in the form 2m + 1 or 2m - 1]
= 2(4k3 + 3k) - 1
Since 2(4k3 + 3k) is a multiple of 2 it is even so by taking away 1 makes it odd, therefore when n=2k the expression is odd.

The second case is when n is odd, then let n=2k + 1 where k is a positive integer (including 0).
Substituting n=2k + 1 gives us:
(2k+1)3 + 3(2k+1) -1
[use the binomial theorem to expand (2k+1)3]
(2k)3 + 3(2k)2(1) + 3(2k)(1)2 + (1)3 + 6k + 3 - 1
=8k3 + 12k2 + 6k + 1 + 6k + 2
=8k3 + 12k2 + 12k + 3
=2(4k3 + 6k2 + 6k) + 3
This is an even number + 3 which gives us and odd number, therefore when n=2k+1 the expression is odd.
Therefore we can conclude that for all n, n3 + 3n - 1 is odd.

Related Maths A Level answers

All answers ▸

Solve the equation sec^2(A) = 3 - tan(A), for 0<= A <= 360 (degrees)


Why is the inverse of a gradient -1/x?


integrate the following: 2x^4 - 4/sqrt(x) +3 with respect to x


Make x the subject of the equation: 5x+1 = 2-4x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences